2009
DOI: 10.1101/gad.1860609
|View full text |Cite
|
Sign up to set email alerts
|

HARPing on about the DNA damage response during replication: Figure 1.

Abstract: In this issue of Genes & Development, four papers report that the annealing helicase HepA-related protein (HARP, also known as SMARCAL1 [SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily a-like 1]) binds directly to the ssDNA-binding protein Replication protein A (RPA) and is recruited to sites of replicative stress. Knockdown of HARP results in hypersensitivity to multiple DNA-damaging agents and defects in fork stability or restart. These exciting insights reveal a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Apparently S-phase checkpoint signaling not only functions as a damage surveillance system but also protects stalled replication forks from collapse by restraining replication origin firing. Besides the role in S-phase checkpoint activation, RPA-ssDNA complex recruits DNA repair proteins such as SMARCAL1 to stalled forks and facilitates the restart of replication forks [26][27][28]. The specific interaction of SMARCAL1 N-terminus with RPA32C is sufficient to localize SMARCAL1 to stalled replication forks to prevent stalled fork collapse by minimizing the accumulation of ssDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently S-phase checkpoint signaling not only functions as a damage surveillance system but also protects stalled replication forks from collapse by restraining replication origin firing. Besides the role in S-phase checkpoint activation, RPA-ssDNA complex recruits DNA repair proteins such as SMARCAL1 to stalled forks and facilitates the restart of replication forks [26][27][28]. The specific interaction of SMARCAL1 N-terminus with RPA32C is sufficient to localize SMARCAL1 to stalled replication forks to prevent stalled fork collapse by minimizing the accumulation of ssDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our group and others defined SMARCAL1 as a replication stress response protein that acts to preserve genome integrity during DNA replication Ciccia et al 2009;Driscoll and Cimprich 2009;Postow et al 2009;Yusufzai et al 2009). Immunofluorescent imaging demonstrated that SMARCAL1 accumulates at damaged replication forks due to its interaction with RPA.…”
Section: Discussionmentioning
confidence: 99%
“…This finding provided unique biochemical evidence for the capability of HLTF and Rad5 to facilitate error-free damage bypass by switching the template from the damaged leading strand to the newly synthesized undamaged nascent strand of the lagging arm. In addition to Rad5 and HLTF, the number of enzymes with proven fork reversal activity is continuously growing (31,33,34,42,43), which raises the possibility that many parallel pathways might exist for fork reversal and template switching. However, it has not been examined what happens to the huge protein complex present at the stalled replication fork, collectively referred to as replication machinery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HLTF, a fork reversal activity has been indicated for a number of other repair proteins such as the Bloom helicase (BLM), HepA-related protein (HARP), and Fanconi anemia complementation group M (FANCM) (31)(32)(33)(34), which suggests that multiple pathways might exist for template switch-dependent error-free DNA damage bypass. However, all previous fork reversal assays were carried out on naked replication fork-like structures, whereas in vivo a stalled replication fork contains several ssDNA-and dsDNA-bound proteins such as the polymerases, RPA, replication factor C (RFC), and PCNA, which can interfere with DNA remodeling.…”
mentioning
confidence: 99%